Junge Laufänderungen des Desaguadero und die Entstehung des Uru-Uru-Sees (bolivianischer Altiplano) - Kessler, Albrecht (ERDKUNDE, 1966)
The lower course of the Desaguadero has experienced marked changes in the last 40 years. In the same period a new lake has appeared which has developed into a stream source. The origins and reasons are illustrated. The morphological situation was the subdued relief of an old sea floor with flat, sunken depressions, formed by the lower Desaguadero as a bank-full stream. An analysis of the water budget of the Desaguadero is presented. Large fluctuations in runoff periodically alter the transporting power of the river, resulting in considerable erosion of the bed and sediment deposition. Several changes in river course have occurred at periods of summer maximum flow and these always orient themselves to the left bank, probably in accordance with the Coriolis effect. The sequence of development of the ice-age Lake Minchin and its effect through the recent course changes of the Desaguadero on the formation of Lake Uru-Uru is compared to similar relationships in the Tarim Basin and the similar result of these climatically conditioned morphogeneses explained.